2022
DOI: 10.31234/osf.io/98d36
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Human morality is based on an early-emerging moral core

Abstract: Cross-cultural research has demonstrated high levels of similarities in the behaviors people find morally right versus wrong (Brown 1991; Curry et al. 2019; Graham et al. 2011). How do humans come to evaluate others’ morally relevant behavior? Here, we review evidence that infants and toddlers evaluate agents who engage in prosocial and antisocial actions. These early-emerging evaluations appear to be rooted in social processes, and by (or before) late in the first year, are based on an understanding of (i) th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…Infants likely do not enter the world as moral 'blank slates,' as they often demonstrate a range of early-emerging proto-moral capacities (Hamlin, 2013;Hamlin et al, 2007;Woo et al, 2022). Newborns, not even two days old, show an early signature of empathy, crying along with the cries of other infants (but not when exposed to silence or simulated cries; Sagi & Hoffman, 1976).…”
Section: Proto-moral Cognitionmentioning
confidence: 99%
See 1 more Smart Citation
“…Infants likely do not enter the world as moral 'blank slates,' as they often demonstrate a range of early-emerging proto-moral capacities (Hamlin, 2013;Hamlin et al, 2007;Woo et al, 2022). Newborns, not even two days old, show an early signature of empathy, crying along with the cries of other infants (but not when exposed to silence or simulated cries; Sagi & Hoffman, 1976).…”
Section: Proto-moral Cognitionmentioning
confidence: 99%
“…Even in humans, these initial core capacities merely serve as a 'blueprint' or 'first draft' for later-emerging social and moral cognition(Ting et al, 2020;Woo et al, 2022).3 That is, the helping behaviour is not extrinsically rewarded by, say, the experimenter or accompanying caregiver.…”
mentioning
confidence: 99%
“…Causal models similarly can produce predictions about action trajectories, but these predictions rely on explicit representations of agents as noisy rational planners whose actions are caused by the expected utilities of different actions, conditioned on their knowledge and beliefs (Baker et al, 2009(Baker et al, , 2017Jara-Ettinger, 2019). In a head to head comparison of these classes of models on tasks and stimuli designed after the infant cognition literature, Shu et al (2021) and Tan et al (2022) found that models with the features described in Sections 3.1-3 (i.e. causal models of planning over utilities that connects physical and mental states) outperformed feedforward predictive models that lack one or more of these features.…”
Section: A Formal Computational Proposalmentioning
confidence: 99%
“…Does this understanding depend on inferred physical parameters (see Sosa et al, 2021;and Shu et al 2020, for evidence from adults)? Is this understanding an elaboration on intuitive psychology (Powell, 2022), or does it instead require additional, distinctively social, representations and computations (Woo et al, 2022)? The classic view, that these two domains of knowledge are informationally encapsulated modules, whose outputs are combined downstream, either in a module specialized for joint reasoning across the domains, or in domain-general reasoning.…”
Section: The Structure Of Domains In Infancy and Beyondmentioning
confidence: 99%
“…We build upon a body of experiments that have found that infants and toddlers show an early capacity for social evaluation: They preferentially look to and reach for agents who help others over agents who hinder others in the pursuit of their goals (13)(14)(15)(16)(17)(18)(19). Studies in this literature have provided evidence that infants and toddlers are sensitive to the intentions underlying social actions (20)(21)(22)(23)(24) and to the contexts in which social actions takes place (e.g., agents' group membership and history of social behavior (25)(26)(27)).…”
Section: Representations Of Action Cost and Evaluations Of Social Act...mentioning
confidence: 99%